A first-principles study of the electrically tunable band gap in few-layer penta-graphene. Issue 26 (25th June 2018) - Wang, Jinjin; Wang, Zhanyu; Zhang, R. J.; Zheng, Y. X.; Chen, L. Y.; Wang, S. Y.; Tsoo, Chia-Chin; Huang, Hung-Ji; Su, Wan-Sheng
Abstract : Our calculations show that the electronic properties of few-layer penta-graphene can obviously be modulated through an external electric field. Abstract : The structural and electronic properties of bilayer (AA- and AB-stacked) and tri-layer (AAA-, ABA- and AAB-stacked) penta-graphene (PG) have been investigated in the framework of density functional theory. The present results demonstrate that the ground state energy in AB stacking is lower than that in AA stacking, whereas ABA stacking is found to be the most energetically favorable, followed by AAB and AAA stackings. All considered model configurations are found to be semiconducting, independent of the stacking sequence. In the presence of a perpendicular electric field, their band gaps can be significantly reduced and completely closed at a specific critical electric field strength, demonstrating a Stark effect. These findings show that few-layer PG will have tremendous opportunities to be applied in nanoscale electronic and optoelectronic devices owing to its tunable band gap.